Steven A. Hunt – D. Francois Tolmie – Ruben Zimmermann (eds.), Character Studies in the Fourth Gospel (WUNT 314; Tübingen: Mohr Siebeck, 2013) - Darowski, Łukasz (The Biblical Annals, 2017)
Book review: Steven A. Hunt – D. Francois Tolmie – Ruben Zimmermann (eds.), Character Studies in the Fourth Gospel (WUNT 314; Tübingen: Mohr Siebeck, 2013). Pp. xvii + 724. 194 EUR. ISBN 978-3-16-152784-5.